PENGEMBANGAN MODEL PEMBELAJARAN MEMBACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN DALAM PEMBELAJARAN BAHASA INGGRIS (Studi pada Mahasiswa Politeknik di Palembang) - Welly Andriansyah; Asari Johar (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
The aim of the research is to generate a reading comprehension model that is able to increase students’ reading comprehension ability at Polytechnics. The study approach used is Research and Development by modifying ten steps of research strategy implementation into three steps. The subjects of study are teachers and students at three Polytechnics in Palembang; Sekayu Polytechnics, Sriwijaya State Polytechnis and Health Polytechnics. Data collection techniques used are observation, questionnaire, interview and test. Research data are analyzed by using qualitative and quantitative analysis technique. The result of data shows that the use of reading strategy of reciprocal teaching combined with peer-teaching method can significantly improve students’ reading comprehension ability. The emerging nurturant effect of implementing reciprocal teaching to reading comprehension course improves social values on students.